Recreating the Medieval Globe : Acts of Recycling, Revision, and Relocation - Weaver, Hannah; Shack, Joseph (Book collections on Project MUSE., 2020)
The creative reuse of materials, texts, and ideas was a common phenomenon in the medieval world. The seven chapters offer here a synchronic and diachronic consideration of the receptions and meanings of events and artifacts, analyzing the processes that allowed medieval works to remain relevant in sociocultural contexts far removed from those in which they originated. In the process, they elucidate the global valences of recycling, revision, and relocation throughout the interconnected Middle Ages, and their continued relevance for the shaping of modernity. The essays examine cases in the Arab.